Affectionate touch and diurnal oxytocin levels: An ecological momentary assessment study - Schneider, Ekaterina; Hopf, Dora; Aguilar-Raab, Corina; Scheele, Dirk; Neubauer, Andreas B.; Sailer, Uta; Hurlemann, René; Eckstein, Monika; Ditzen, Beate (eLife, 2023)
Background:. Affectionate touch, which is vital for mental and physical health, was restricted during the Covid-19 pandemic. This study investigated the association between momentary affectionate touch and subjective well-being, as well as salivary oxytocin and cortisol in everyday life during the pandemic. Methods:. In the first step, we measured anxiety and depression symptoms, loneliness and attitudes toward social touch in a large cross-sectional online survey (N = 1050). From this sample, N = 247 participants completed ecological momentary assessments over 2 days with six daily assessments by answering smartphone-based questions on affectionate touch and momentary mental state, and providing concomitant saliva samples for cortisol and oxytocin assessment. Results:. Multilevel models showed that on a within-person level, affectionate touch was associated with decreased self-reported anxiety, general burden, stress, and increased oxytocin levels. On a between-person level, affectionate touch was associated with decreased cortisol levels and higher happiness. Moreover, individuals with a positive attitude toward social touch experiencing loneliness reported more mental health problems. Conclusions:. Our results suggest that affectionate touch is linked to higher endogenous oxytocin in times of pandemic and lockdown and might buffer stress on a subjective and hormonal level. These findings might have implications for preventing mental burden during social contact restrictions. Funding:. The study was funded by the German Research Foundation, the German Psychological Society, and German Academic Exchange Service.